Larotrectinib as an Effective Therapy in Congenital Infantile Fibrosarcoma: Report of Two Cases - Lapeña, Lucas Moratilla; Caldas, Maria Carmen Sarmiento; Ramírez, Carla; Basilio, María San; Junco, Paloma Triana; Rodríguez-Laguna, Lara; Martínez-González, Victor; Marín-Manzano, Elena; Perez-Martinez, Antonio; Lopez-Gutierrez, Juan Carlos (European Journal of Pediatric Surgery Reports, 2022)
Congenital infantile fibrosarcoma (CIF) is a rare tumor in children that occurs in the first years of life. It usually arises in the extremities but some cases affect the trunk, neck, abdomen, or retroperitoneum. Surgical resection has been traditionally the treatment of choice but the development of genomic analysis and targeted therapies has shed light on new therapeutic options.We present two patients with a congenital mass, one in the abdominal cavity (1-month-old) and the second in the left lower extremity respectively (2-months-old). In both cases, the clinical and radiological findings showed heterogeneous masses with rapidly progressive growth. MRI in the first patient exhibited an abdominal mass surrounding the aorta and inferior vena cava associated with a giant infrarenal aortic aneurysm. CT-guided biopsy was performed with pathological findings of fibrosarcoma and ETV6-NTRK3 gene fusion. The second patient underwent open biopsy also with histopathological diagnosis of fibrosarcoma and the same mutation in the TRK gene (NTRK3). Targeted therapy with a specific TRK inhibitor, larotrectinib, was started in both patients. Periodical controls were made by ultrasound or MRI, and after a few weeks of treatment, both children showed significant decrease in the mass. By the second and third months after starting the treatment, both tumors disappeared. The first patient is now 15-months-old and the second one is 8-months-old.Larotrectinib is a novel targeted therapy with excellent results in CIF but long-term outcomes are limited to establish it as a gold standard treatment.
Keywords: congenital infantile fibrosarcoma; larotrectinib; children tumor